FSKTM Database for post graduate students (PGSDB) / Ardit H. Llazani - Ardit, H. Llazani (2001)
In this paper I categorize and explain the usage and the process of the construction, of FSKTM Database for post-graduate students, (PGSDB) a web based application. I explain the process in simple terms for the person who might not be familiar with the data. The paper begins with a introduction of the system to familiarize the reader with the role of the system and its objectives, then a review of the literature and an brief analysis of it gives an idea of what material was referred. The following sections explore in more details the components of the system and their construction process. Three aspects used in conjunction indicate the project novelty: firstly, the systematic explanation and the description of the system, secondly the tools and the reason of their usage thirdly, the design of the system. I conclude with the development phase and the description of the system that ends with the user's manual.